2007
DOI: 10.1097/ana.0b013e31811f3feb
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fentanyl and S(+)-ketamine on Cerebral Hemodynamics, Gastrointestinal Motility, and Need of Vasopressors in Patients With Intracranial Pathologies

Abstract: In neurosurgical patients, opioids are administered to prevent secondary cerebral damage. Complications often related to the administration of opioids are a decrease in blood pressure affording the use of vasopressors and intestinal atonia. One alternative approach to opioids is the application of S(+)-ketamine. However, owing to a suspected elevation of intracranial pressure (ICP), the administration of S(+)-ketamine has questioned for a long time. The aim of the present study was to evaluate ICP, gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 48 publications
1
88
0
1
Order By: Relevance
“…These results have been called into question in the last 20 years because there are no data supporting these conclusions, and the original case reports had no comparison control group. Most research has supported that ketamine has a neutral or beneficial effect on CPP in patients with TBI and other neurologic insults (48)(49)(50)(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have been called into question in the last 20 years because there are no data supporting these conclusions, and the original case reports had no comparison control group. Most research has supported that ketamine has a neutral or beneficial effect on CPP in patients with TBI and other neurologic insults (48)(49)(50)(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a regularly taught principle that ketamine will cause patients to become hypertensive and tachycardic, multiple studies have examined the use of ketamine for sedation and induction for RSI and found that ketamine, alone or in combination with other drugs, maintains hemodynamic neutrality without causing severe hypertensive or tachycardic responses (50,(57)(58)(59)(60)(61)(62)(63)(64).…”
Section: Resultsmentioning
confidence: 99%
“…A small decrease in ICP with no change in mean arterial pressure or CPP was noted. 20 Schmittner et al 21 compared ketamine to fentanyl in combination with methohexitone for sedation in 24 ventilated intensive care unit patients with traumatic brain injury or aneurysmal subarachnoid hemorrhage. Patients who received ketamine had a tendency to require less norepinepherine to maintain CPP and did not have elevated ICP.…”
Section: Discussionmentioning
confidence: 99%
“…84 Finally, in extreme circumstances, ketamine for analgesia in the ICU may be warranted, although there are no Level I studies specific to ICU. 85,86 Sedation In addition to adequate analgesia, a smaller proportion of patients will require the addition of medication for sedation. In general, when sedation is required, light sedation is preferred.…”
Section: Medications For the Management Of Pain Agitation And Delirmentioning
confidence: 99%